Bitterman's field guide to bitters and amari : 500 bitters, 50 amari : 123 recipes for cocktails, food & homemade bitters - Bitterman, Mark; Schloss, Andrew, 1951- (Andrews McMeel Publishing, 2015)
"The most comprehensive handbook available on selecting, understanding, mixing, and cooking with bitters, for everyone from professional bartenders and chefs to casual entertainers and home cooks." --